Nutritional values of wild rusa deer (Cervus timorensis) venison - Jamal, Y; Semiadi, G; Hamsun, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
Until 2002, the level of protein consumption from red meat origin by the Indonesian people was only 51.5% from the national target. The reasons for this condition were due to limited resources of domesticated animals and low income of many suburb people to buy red mead. One alternative in supplying the gap of protein consumption is by utilizing local prospective wildlife animals, such as deer. This species is widely distributed among the islands in Indonesia. In order to understand more on the quality of tropical rusa venison (Cervus timorensis), a study was conducted in Palu district, Southeast Sulawesi by collecting venison from hunters. The results showed there was no significant difference on cooking lost among the carcass parts (hind leg, front leg and saddle), with the range between 30.3 to 33.0%. There were also no significant differences on the gross energy, protein, ash, fat and phosphor values among the carcass parts. The contents of sodium , ferum and calcium were significantly different at p<0.05. In fatty acid contents, there was no interaction between the carcass parts and fatty acid groups, however among the fatty acid groups there was a significant difference (p<0.001) on the content. Palmitic and stearic acid had the highest contents (>9.5% DM), compared to other groups (<4.0% DM). In amino acid contents , it showed no interaction between the carcass parts to amino acid groups, however there was a significant difference among the amino acid groups. Glutamic acid had the highest level (15.74%DM), where as others were ranged between 2.7 to 7.6% DM. (Animal Production 7(1): 46-51 (2005)Â Keywords: Rusa deer, Cervus timorensis, venison, nutritional values